Segurança Alimentar em Unidades de Alimentação e Nutrição. - Rodrigues, Kelly Lameiro (2010)
In recent years there has been a large increase in the number of foodservice establishments, especially in the area of collective meals. However, this increase does not always come with the concern about the sanitary quality of meals served. The use of quality control tools in foodservice units is of fundamental importance for the production of safe meals from a microbiological standpoint, besides being a requirement of Brazilian legislation. In the first article the adoption of Good Manufacturing Practices (GMP), Sanitation Standard Operating Procedures (SSOP) and of the Hazard Analysis and Critical Control Points (HACCP) system in institutional foodservice operations in the city of Caxias do Sul RS was evaluated; the results showed the existence of deficiencies in the implementation and use of these quality control tools in food preparation, hot holding and distribution. In the second article the hygienic and sanitary conditions and the effect of implementation of a Prerequisite Program (RRP) in the practices of an institutional foodservice unit in southern Brazil were evaluated; the results showed that GMP arising from PRR may promote the conditions for production of safe meals. In the third article the aim was to validate the procedures for cleaning vegetables served raw in salads and for transport of hot food preparations in an institutional foodservice in the city of Pelotas. The temperatures of the hot food preparations transported, as well as their holding time, were kept within the safety limits prescribed by Brazilian legislation from the end of the cooking process up to the end of the service period. However, high coliform counts of some vegetable samples after hygienization suggest that the procedure need to be adjusted.